2021
DOI: 10.1186/s12888-021-03131-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional states of different obesity phenotypes: a sex-specific study in a west-Asian population

Abstract: Background The present study aimed to investigate the associations of obesity phenotypes with depression, anxiety, and stress symptoms among adults in the Tehran Lipid and Glucose Study (TLGS). Methods Depression, anxiety, and stress levels of participants from the TLGS were examined among different obesity phenotypes in this cross-sectional study. Obesity was defined as body mass index (BMI) ≥30 kg/m2, and metabolically unhealthy s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…After carefully screening of 453 full texts, we also excluded 435 more studies because they investigated the association between metabolic phenotype with an outcome other than mental health or HRQoL, or were animal or in vitro studies in design, editorial, and reviews. Finally, 18 different studies [ 1 , 4 8 , 12 , 22 32 ] with a total of 3,929,203 participants, published between 2008 and 2021, were eligible for the systematic review. The flow chart of study selection is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After carefully screening of 453 full texts, we also excluded 435 more studies because they investigated the association between metabolic phenotype with an outcome other than mental health or HRQoL, or were animal or in vitro studies in design, editorial, and reviews. Finally, 18 different studies [ 1 , 4 8 , 12 , 22 32 ] with a total of 3,929,203 participants, published between 2008 and 2021, were eligible for the systematic review. The flow chart of study selection is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between obesity phenotypes and quality of life (QoL) and mental health has been examined in some literature [ 4 7 ]; but, QoL and mental health issues associated with obesity phenotypes have not been studied as thoroughly as physical difficulties [ 8 ]. Despite a previous meta-analysis of prospective studies suggesting that individuals with higher body mass index (BMI) have a greater chance of developing depression [ 9 ], some studies find no relationship between obesity and depression [ 10 ], and one study reported lower mental health risks associated with higher BMI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no standardized definition of MHO, several characteristics are common to all MHO individuals, including low visceral mass, high insulin sensitivity and normal arterial blood pressure [ 87 ]. Individuals with MHO have lower levels of depressive symptoms [ 88 ], stress and anxiety [ 89 , 90 ] and higher well-being scores [ 90 ] than individuals with metabolically unhealthy obesity. Some studies have even found that individuals with MHO did not differ from the individuals with normal metabolically healthy weights in terms of the risk of depressive symptoms [ 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with MHO have lower levels of depressive symptoms [ 88 ], stress and anxiety [ 89 , 90 ] and higher well-being scores [ 90 ] than individuals with metabolically unhealthy obesity. Some studies have even found that individuals with MHO did not differ from the individuals with normal metabolically healthy weights in terms of the risk of depressive symptoms [ 88 , 89 , 90 ]. In their 16-year follow-up study, Hinnouho et al concluded that the metabolic health status predicts depressive symptoms at the start of the follow-up but that obesity predicts a poorer evolution of depressive symptoms over time only in metabolically unhealthy individuals [ 88 ].…”
Section: Discussionmentioning
confidence: 99%